Operational Audit Analysis In Testing The Effectivieness Of Control Of Operating Expenses At Foundation B By KAP DE - Natalia Dwi Wulandari; Sri Trisnaningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One way management can control the foundation better is by controlling operating costs as effectively and effectively as possible. An operational audit is a systematic process used to assess how effective and efficient operations are under internal supervision. This audit report is submitted to the management along with recommendations for improvement. This study aims to find a more efficient way to control operational costs through operational audits. The research method used is using a qualitative descriptive method. Based on the research, it can be concluded that the Foundation's operational audit has been carried out independently and in accordance with applicable audit theories and standards. The operational auditor remains objective and can carry out his responsibilities honestly and carry out all his or her abilities in auditing. In addition, operational auditors are still reflected in the position of the audit unit.